Sustainable land management & organic amendments for crop production & restoration in drylands - ICARDA's experience - Devkota Wasti, Mina Kumari (2023)
F2R-CWANA WP3 scientist Mina Devkota Wasti was invited to speak at the "The Perspective of Future Technologies for Soil Amendments" organised by the Palladium Group about the ICARDA's experience in sustainable land management, organic amendments for crop production, and restoration in the drylands (through F2R-CWANA and EiA Initiatives).